2017
DOI: 10.3390/ijerph15010039
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Causal Impact of Proximity to Gold and Copper Mines on Respiratory Diseases in Chilean Children: An Application of Targeted Maximum Likelihood Estimation

Abstract: In a town located in a desert area of Northern Chile, gold and copper open-pit mining is carried out involving explosive processes. These processes are associated with increased dust exposure, which might affect children’s respiratory health. Therefore, we aimed to quantify the causal attributable risk of living close to the mines on asthma or allergic rhinoconjunctivitis risk burden in children. Data on the prevalence of respiratory diseases and potential confounders were available from a cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(57 reference statements)
1
10
1
1
Order By: Relevance
“…The only exception were women aged 70–74 years reporting higher EQ VAS values than their male counterparts. Similar findings were described by Huber et al [ 28 ] for Germany.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The only exception were women aged 70–74 years reporting higher EQ VAS values than their male counterparts. Similar findings were described by Huber et al [ 28 ] for Germany.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies found that higher age is significantly associated with lower HRQoL as measured by the EQ-5D-5L [ 14 , 19 , 27 ]. Moreover, there is further evidence to suggest that variation in HRQoL is large in the elderly, which is even more pronounced in the oldest old [ 28 , 29 ]. With regard to Germany, two sets of preference-based reference values were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are several sources of air pollutants with an impact on the respiratory health of exposed workers (power plants, cement factories, construction industries, petrochemical industries, mining, etc. ), the emissions of particulates from quarries are quite high [ 3 , 4 , 5 , 6 , 7 ]. Individuals exposed to high particulate matter (PM 2.5 in particular) levels at their working or living environments are at a higher risk of developing a number of respiratory disorders, such as chronic airway inflammatory diseases (bronchitis, emphysema, silicosis) and lung cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the health impacts of working in stone quarry settings are well documented [ 4 , 5 ]. For instance, epidemiological studies have supported the association between respiratory impairment and occupational exposure to dust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation